Pemanfaatan Perangkat Lunak Akuntansi untuk Menghasilkan Laporan Keuangan pada PT. PNM ULaMM PTPM Pontianak - Sarwani Sarwani; Nurfia Oktaviani Syamsiah; Fara Dina (Universitas Bina Sarana Informatika, 2018)
Long time-consuming reporting is an issue that always arises on conventional transaction data processing. Especially in accounting systems that have output more than one type of report. In addition, the pressure of work often makes an accountant become less concentration that can lead to mistakes in journalizing, posting to create reports. For that done a qualitative research with case study method of financial data at PT. PNM ULaMM PTPM Pontianak with the aim to verify the reliability of an accounting software with the advantage of time efficiency. The results can be seen that accounting software (Accounting Information System) is able to process data transactions quickly, precisely and accurately and generate relevant reports. Key Word: Accounting Information System, Zahir Accounting, PT. PNM